Image Dehazing Techniques: A Survey - HARPREET kAUR (International Journal of Advanced Science and Technology, 2020)
Dehazing is a mechanism of eliminating the degration from the picture to enhance its clearity.Sincepresence of haze in the atmosphere introduces some kind of noise in an image or it simply diminishes the visibility of a scene,it becomes vital to remove this problem. Remote sensing deals with the usage of satellite or airplaneimages, which are based on sensor technology for the detection of various resources on earth such as its surface, ambiance and data about oceans. However, this technique of sensing the resources or objects faces certain tribulations regarding the quality of the image. In thispaper,detailed information is given of the haze noise along with the various techniques to eliminatethis noise from an image that can be used in the future or are already in use.